(untitled) (Ustozlar uchun, 2025)
This article examines the topic “How AI Practice Improves Speech” and scientifically analyzes the impact of artificial intelligence on speech development, pronunciation correction, communication skills development, and language learning. Today, AI technologies - virtual interlocutors, chatbots, voice analysis platforms, automatic pronunciation checkers, and real-time echo systems - serve as effective tools for speech development. AI systems automatically detect grammatical errors, pronunciation errors, intonation, and rhythm problems in a student’s speech, immediately offer the correct option, and create individual exercises. This process allows students to practice more, learn independently, and consistently improve their speech. At the same time, AI-based speech simulators create a communication environment close to real life for those learning a foreign language. The article extensively discusses the impact of AI on speech development, its advantages, practical examples, efficiency factors and limitations. The results of the study show that AI technologies can significantly improve speech skills in a short time.